2013
DOI: 10.1063/1.4813551
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in resistive switching of Ba-doped BiFeO3 films

Abstract: We investigate the resistive switching behavior of Ba-doped BiFeO3 (BBFO) films grown on single crystalline SrTi0.99Nb0.01O3 substrates. Observation of diode like I-V behavior and reduction in VC with Ba-content in BBFO films have been understood in the context of modifications in its energy band diagram. Also, I-V curves exhibit hysteresis which has been explained on the basis of migration and recombination of oxygen vacancies under field conditions. Furthermore, increment in Ba-content improves the retention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…So, in recent years, a series of interesting electrical properties have been extensively investigated. [8][9][10][11] Variations in the optical band gap and conductivity at domain walls was also observed in BFO films, 12 which indicates the possibility of stabilizing some conducting sates in these multiferroic materials. 7 Moreover, reversible resistive switching behaviors have been reported in epitaxial BFO thin films, BFO nano-islands, Ba doped BFO films, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…So, in recent years, a series of interesting electrical properties have been extensively investigated. [8][9][10][11] Variations in the optical band gap and conductivity at domain walls was also observed in BFO films, 12 which indicates the possibility of stabilizing some conducting sates in these multiferroic materials. 7 Moreover, reversible resistive switching behaviors have been reported in epitaxial BFO thin films, BFO nano-islands, Ba doped BFO films, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Doping the ferroelectric layer with appropriate elements is the simplest way to improve the RS performance of ferroelectric heterostructures. In BiFeO 3 /Nb:SrTiO 3 heterostructures, an optimal ON/OFF ratio of 2500 was achieved, and the switching voltage was reduced to 0.68 V by doping 20% Ba into the BiFeO 3 layer . The increase in ON/OFF ratio could be attributed to the increase of the oxygen vacancies in the Ba‐doped BiFeO 3 layer.…”
Section: Approaches To Improve Rs Propertiesmentioning
confidence: 99%
“…5 BiFeO 3 (BFO) is a well known widely studied multiferroic, having large ferroelectric polarization ($ 100 lC/cm 2 ), magnetization ($ 1 l B /Fe), and resistive switching ($ 2500 on/off ratio) at room temperature and hence a suitable candidate for technological applications. [6][7][8] These three functionalities of BFO provide an opportunity to design novel BFO based multifunctional devices but its usefulness in device applications is hindered by factors, such as leakage current due to oxygen vacancies, weak magnetic behaviour due to inhomogeneous cycloidal spin spiral arrangement, Bi-volatility, high coercive field, etc. [9][10][11][12] To overcome one or more of these factors, studies have been reported, which focused on the synthesis of polycrystalline bulk and thin films of BFO forms using different methods or by iso-or aliovalent chemical doping at either Bi or Fe-sites.…”
mentioning
confidence: 99%
“…16 Moreover, naturally formed oxygen vacancies in divalent (Ca, Ba) doped BFO films are responsible for the resistive switching. 4,8 In order to understand the local electronic structure and strain state modification and various chemical states of constituent in the BFO films, X-ray based techniques, such as reciprocal space mapping (RSM) and Near-edge X-ray absorption Fine structure (NEXAFS) spectroscopy have been extensively used. NEXAFS is element sensitive technique, which provides information about local electronic structure of the materials including electronic state, charge transfer, type of bonding, and hybridization, while RSM gives knowledge about the strain state in the film.…”
mentioning
confidence: 99%